Cotton revolution and widow chastity in Ming and Qing China - Liang, Ruobing; Wang, Xiaobing; Yamauchi, Futoshi (Agricultural and Applied Economics Association, 2021)
The historical practice of widow chastity in China is regarded as an outcome of traditional Confucian thought. This study examines how economic factors played key roles in the formation of this cultural tradition by studying the causality between technological progress in the cotton textile sector and the increase in the number of widow chastity cases between the Ming and Qing Dynasties. We find that the incidence of widow chastity increased significantly with rapid technological change in the cotton textile sector and increased demands for female labor. This result remains robust when the issues of widow chastity selection and alternative economic and cultural channels are addressed.